The Relationship Between Health Locus of Control and Diet Compliance in Diabetes Patients Type 2 Mellitus at Tilongkabila Community Health Center - Salwa Aulia Madiha; Ita Sulistiani; Gusti Pandi Liputo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the relationship between Health Locus of Control and compliance with diet in Diabetes Mellitus (DM) patients at Tilongkabila Community Health Center. This research is a quantitative study. The research design I used in this study is correlational with a cross-sectional approach, which is carried out to see the relationship between the variables found. The level of dietary compliance in type 2 diabetes patients at the Tilongkabila Community Health Center shows that of the 74 respondents, there is 1 respondent (1.4%) who is not compliant, 57 respondents (77.0%) are quite compliant, and 16 respondents (21.6%) are compliant. The level of Health Locus of Control (HLOC) in the respondents consists of 13 respondents (17.6%) in the low category, 47 respondents (63.5%) in the moderate category, and 14 respondents (18.9%) in the high category. There is a relationship between Health Locus of Control and dietary compliance, where patients with a better HLOC show a tendency for higher dietary compliance.